Pengaruh Strategi, Inovasi dan Pengembangan UMKM Pada Bidang Kuliner Di Kota Bandung Pada Masa Covid-19 - Nawawi, Sophian; Mufti, Rifki Muhammad; Ayu Mega, Anak Agung (Asosiasi Ahli Administrasi Indonesia, 2021)
This research was conducted to determine the efforts and steps taken by entrepreneurs, Micro, Small and Medium Enterprises (MSMEs) that can be applied to improving marketing performance during the Covid-19 period. Based on the results of this study, it can provide a broad understanding of strategy and innovation and development that can be taken into consideration for research on the needs of MSME consumers in Bandung during the COVID-19 period. This research identifies problems faced by culinary MSMEs during the COVID-19 Pandemic and analyzes them using quantitative descriptive methods operated using SPSS 24 then formulates strategic models, innovations, and developments that need to be done to overcome the impact of COVID-19 which then will be the results of this research. The weaknesses faced by MSMEs in increasing business capabilities are very complex, coupled with the current environmental conditions which make it very possible for MSMEs to experience losses or bankruptcy. MSMEs here are required to always look for new ways, opportunities, or other alternatives that can be done to maintain their business and sales.